Partial-thickness Articular Surface Rotator Cuff Tears: An All-inside Repair Technique - Spencer, Edwin E. (Springer-Verlag, 2010)
BACKGROUND: Treatment of partial-thickness articular surface rotator cuff tears varies from simple débridement with or without an acromioplasty to various repair techniques. These repair techniques have included in situ transtendinous methods, as well as completion of the tear and repairing the full-thickness defect. The transtendinous techniques can be associated with stiffness and completing the tear takes down normal intact tissue. Therefore, a technique was developed that repairs the articular-side partial- thickness rotator cuff tears with an all-inside approach that does not violate the intact bursal tissue and does not complete the tear. QUESTIONS/PURPOSES: To compare the preoperative and postoperative Penn shoulder scores (PSS) associated with an in situ all-inside repair technique and the effects of such a repair on postoperative stiffness. METHODS: Twenty patients with partial-thickness articular rotator cuff tears greater than 50% of the width of the tendon repaired with an all-inside repair technique were retrospectively reviewed. Two of the patients were high school athletes and the rest self-described as recreational athletes. The minimum followup was 16 months (average, 29 months; range, 16–41 months). A validated outcome measure (PSS) was used to assess clinical outcome, and postoperative ROM was measured. RESULTS: The average PSS score improved from 74 (range, 56–84) to 92 (range, 86–99). All but one patient was able to return to the same level of play or higher. CONCLUSIONS: In situ repairs of partial-thickness articular surface tears using an all-inside approach resulted in a substantial increase in PSS with no cases of major postoperative clinical stiffness. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.